Safety considerations of current drug treatment strategies for nosocomial pneumonia. Issue 2 (1st February 2021) - Ceccato, Adrian; Di Giannatale, Pierluigi; Nogas, Stefano; Torres, Antoni
ABSTRACT: Introduction : Nosocomial pneumonia unfortunately remains a frequent event for which appropriate antibiotic treatment is central to improving outcomes. Physicians must choose an early and appropriate empirical treatment, basing their decision on the safety profile and possible side effects. Areas covered : In this review, we analyzed the safety profiles of the most common antimicrobials for treating nosocomial pneumonia. Beta-lactams are used most often for these infections, with a high percentage (6% to 25%) of patients reporting allergy or hypersensitivity reactions; however, exhaustive evaluation is key because it seems possible to de-label as many as 90% by proper assessment. Combinations including a beta-lactam are recommended in patients with risk factors for drug-resistant microorganisms and septic shock. Although aminoglycosides are safe for 3–5 days of therapy, renal function should be monitored. Fluoroquinolones must also be used with care given the risk of collagen degradation and cardiovascular events, mainly aneurysm or aortic dissection. Linezolid or vancomycin are both viable for the treatment of methicillin-resistant Staphylococcus aureus, but linezolid seems to be the superior option. Antibiotic stewardships programs must be developed for each center. Expert opinion : Choosing the most appropriate antimicrobial based on information from national and international guidelines, local microbiology data, and stewardship programs may reduce the use of broad-spectrum antibiotics. Daily assessment for the emergence of adverse events related to antimicrobial use is essential.